2019
DOI: 10.1002/aur.2102
|View full text |Cite
|
Sign up to set email alerts
|

Early processing (N170) of infant faces in mothers of children with autism spectrum disorder and its association with maternal sensitivity

Abstract: Individuals with autism spectrum disorder (ASD) exhibit impaired adult facial processing, as shown by the N170 eventrelated potential. However, few studies explore such processing in mothers of children with ASD, and none has assessed the early processing of infant faces in these women. Moreover, whether processing of infant facial expressions in mothers of children with ASD is related to their response to their child's needs (maternal sensitivity [MS]) remains unknown. This study explored the N170 related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…An interesting phenomenon is that the parents of ASD children do not seem to show the effect of left hemisphere lateralization in facial expression processing. While their N170 amplitude is larger in their right hemisphere than in their left hemisphere ( Márquez et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…An interesting phenomenon is that the parents of ASD children do not seem to show the effect of left hemisphere lateralization in facial expression processing. While their N170 amplitude is larger in their right hemisphere than in their left hemisphere ( Márquez et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, studies involving passive viewing frequently report no emotion effects on the N170 in mothers (Lowell et al, 2020(Lowell et al, , 2021Malak et al, 2015;Maupin et al, 2019;Rutherford, Byrne, et al, 2017;Rutherford et al, 2019;Rutherford, Maupin, et al, 2017a;Wall et al, 2022), whereas emotion recognition tasks in which participants categorize infant emotions during each experimental trial have frequently reported associations between infant facial expression and maternal N170 responses (Bernard et al, 2018;Ma et al, 2017;Márquez et al, 2019;Proverbio et al, 2006). Lowell et al (2021) posits that these findings may reflect intentional directing of attention to the infant face stimuli required by emotion recognition tasks, and future work directly comparing different experimental tasks is required to support this proposal.…”
Section: Discussionmentioning
confidence: 99%
“…However, variability in experimental approaches may contribute to reported differences. For example, studies involving passive viewing frequently report no emotion effects on the N170 in mothers (Lowell et al., 2020, 2021; Malak et al., 2015; Maupin et al., 2019; Rutherford, Byrne, et al., 2017; Rutherford et al., 2019; Rutherford, Maupin, et al., 2017a; Wall et al., 2022), whereas emotion recognition tasks in which participants categorize infant emotions during each experimental trial have frequently reported associations between infant facial expression and maternal N170 responses (Bernard et al., 2018; Ma et al., 2017; Márquez et al., 2019; Proverbio et al., 2006). Lowell et al.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen of 21 studies included parents, beginning as early as pregnancy up to parents with children who were on average 5 years old. These 18 studies compared maternal neural response to infant/child facial expressions (crying, laughing, and/or neutral faces) between groups, such as parents compared with nonparents (Noll et al, 2012 ; Peltola et al, 2014 ; Proverbio et al, 2006 ), CPS-referred mothers receiving a parenting intervention versus control intervention and nonreferred mothers (Bernard et al, 2015 ), mothers with substantiated neglect versus control mothers (Rodrigo et al, 2011 ), mothers who did and did not smoke (Rutherford, Maupin, et al, 2017a ), mothers with and without children with autism spectrum disorder (Márquez et al, 2019 ), and securely attached vs. insecurely attached mothers (Fraedrich et al, 2010 ; Leyh et al, 2016 ). Some studies also examined differences within person, such as pregnancy vs. postpartum (Dudek et al, 2020 ), responses after administration of intranasal oxytocin compared to placebo (Peltola et al, 2018 ), or own infant versus unfamiliar infant faces (Doi & Shinohara, 2012 ).…”
Section: Racial/ethnic Representation In Previous Erp Studies Examini...mentioning
confidence: 99%